Gender-Based Violence: How South Sudan is fighting back - Nyakomi Adwok (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2023)
From the first Sudanese civil war in 1955 to cyclical conflicts post-independence, the scarlet cord of violence is inextricably woven into the history of South Sudan. Within this shadow of perpetual destabilisation lies a more entrenched issue: gender-based violence (GBV). The United Nations (UN) defines GBV as "harmful acts directed at an individual or a group of individuals based on their gender," which is "rooted in gender inequality, the abuse of power, and harmful norms." This definition acknowledges the fact that while women and girls suffer disproportionately from GBV, men and boys can also be targeted. GBV includes a variety of violations, from physical, sexual, and emotional violence to female genital mutilation and human trafficking. It also encompasses threats of violence, financial abuse, coercion, and manipulation.